2017
DOI: 10.1002/adma.201704585
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Bending of ReS2 Nanowalls

Abstract: Among the variety of stimuli-responsive materials, temperature-responsive materials (TRMs) can adapt to the surrounding environment in the presence of a thermal stimulus, and they have attracted considerable attention in sensors, actuators, and surface engineering. However, polymers, as the most representative TRMs, are far from ideal with respect to long-term reliability and durability. Here, for the first time, an inorganic material, ReS , is analyzed, which possesses an unexpected temperature-responsive beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…1f, the interlayer distance was measured to be 0.62 nm, corresponding to the (001) plane of ReS 2 . [19][20][21] X-ray photoelectron spectroscopy (XPS) was utilized to examine the elemental compositions and bonding configurations. To evidence the existence of N, commercial ReS 2 powder was also characterized as a comparison object.…”
Section: Resultsmentioning
confidence: 99%
“…1f, the interlayer distance was measured to be 0.62 nm, corresponding to the (001) plane of ReS 2 . [19][20][21] X-ray photoelectron spectroscopy (XPS) was utilized to examine the elemental compositions and bonding configurations. To evidence the existence of N, commercial ReS 2 powder was also characterized as a comparison object.…”
Section: Resultsmentioning
confidence: 99%
“…6,[8][9][10][11][12][13][14] The most efficient singlejunction OPV to date has reached a power conversion efficiency of 14% using the NFA ITIC-4F. 15 Despite this rapid rise in efficiency, a fundamental understanding of the charge generation mechanism is still lagging behind.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Recently, it is confirmed that a new type of TMD, rhenium disulfide (ReS 2 ), has extraordinary photocatalytic properties due to its remarkable electron-hole separation and is a promising photocatalyst for hydrogen production. [20][21][22][23][24] With this in mind, we expect ReS 2 to act as a cocatalyst to further enhance the photocatalytic performance, which may provide new opportunities for photocatalytic H 2 evolution. [25][26][27][28][29][30][31] However, to the best of our knowledge, it has rarely been reported as a cocatalyst for photocatalytic hydrogen production.…”
Section: Introductionmentioning
confidence: 99%